AN EXPLORATION OF PRAGMATIC MARKERS IN MULTILINGUAL WORKPLACE COMMUNICATION - Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
This research explores the intricate use of pragmatic markers in multilingual workplace communication, delving into the dynamics of communication within the context of globalization and technological advancements. Drawing from a rich theoretical foundation, the study investigates the role of pragmatic markers in managing face-threatening acts, resolving conflicts, and preserving relationships in a multicultural workplace. Recent research underscores the increasing relevance of pragmatic markers in the globalized workforce and the impact of electronic communication on their use. Additionally, the study highlights the necessity for pragmatic marker-focused training programs to enhance intercultural communication. By examining the novel insights derived from this research, we gain a deeper understanding of how pragmatic markers function in multilingual workplace interactions, particularly in the era of electronic communication, thereby contributing to more effective cross-cultural understanding.